Manajemen Kepemimpinan Kepala Madrasah dalam Meningkatkan Kinerja Guru di MTs. Nurul Falah Pasanggrahan Petir Serang - Yayah Faoziyah; Muslihun Muslihun (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study is a qualitative research employing a case study approach to explore the leadership management of a madrasah principal in improving teacher performance. The data analysis technique used consists of four main steps: data collection, data reduction, data presentation, and drawing conclusions. To ensure the validity and reliability of the findings, source triangulation was applied. The research findings reveal that the madrasah principal plays a multifunctional role encompassing that of a manager, supervisor, and motivator, all of which are central to the effective management of the institution. The principal’s leadership is characterized by a strong orientation toward the achievement of the institutional vision, optimal resource management, and the establishment of a conducive and productive learning environment. Several strategic efforts have been implemented to enhance teacher performance, including the enforcement of work discipline, organizing continuous professional development through teacher training, offering rewards and incentives for achievements, cultivating positive attitudes and mental resilience among staff, and providing financial support to facilitate teaching activities. These strategies reflect a proactive and visionary leadership model that emphasizes communication, motivation, and collaboration. The effectiveness of this leadership approach is evidenced by the significant improvement in teacher performance, contributing to the overall enhancement of educational quality within the madrasah. This study concludes that leadership which is visionary, communicative, and supportive is essential in fostering an environment that promotes teacher development and institutional progress. The results of this research provide valuable insights for education stakeholders, particularly in Islamic educational institutions, on how strategic leadership practices can drive meaningful change and improve educational outcomes. This study also highlights the importance of ongoing support, recognition, and empowerment of teachers as key elements in building a high-performing and motivated teaching workforce.